URGENSI PEMBENTUKAN MAJELIS HAKIM AD HOC MAHKAMAH KONSTITUSI DALAM PERKARA JUDICIAL REVIEW: The Urgency of Forming an Ad Hoc Panel of Judges at the Constitutional Court in Judicial Review Cases - Alghifari, Muh; Mallongi, Andi Agung; Nuraiman, Nuraiman (Constitution Journal, 2024)
This research employs a juridical-normative legal research method with a statutory approach and a case approach to explore the procedure for establishing the Ad Hoc Panel of the Constitutional Court as a response to violations of the principle of nemo judex in causa sua. The aim of this research is to outline the procedure for establishing the Ad Hoc Panel of the Constitutional Court and its implications for maintaining the integrity of the Constitutional Court. The formation of the Ad Hoc Panel of the Constitutional Court is a relevant alternative in this context. Ad Hoc Judges, selected based on their expertise and specialized experience in constitutional law, can assist in handling complex or sensitive cases without conflicts of interest that would compromise the judicial process. These measures are expected to enhance the integrity and credibility of the Constitutional Court, enabling it to fulfill its functions as an upholder of the constitution free from external influence, and strengthen public trust in the constitutional justice system. Despite challenges in implementing this mechanism, such as the proper selection of Ad Hoc Judges and oversight mechanisms, these steps are crucial in ensuring the enforcement of the principle of nemo judex in causa sua Abstrak Penelitian ini menggunakan metode penelitian hukum yuridis normatif dengan pendekatan perundang-undangan (statue approach) dan pendekatan kasus (case approach) untuk mengeksplorasi prosedur pembentukan Majelis Hakim Ad Hoc Mahkamah Konstitusi sebagai respons terhadap pelanggaran asas nemo judex in causa sua. Tujuan penelitian ini adalah menguraikan prosedur pembentukan Majelis Hakim Ad Hoc Mahkamah Konstitusi serta implikasinya dalam menjaga integritas Mahkamah Konstitusi. Pembentukan Majelis Hakim Ad Hoc Mahkamah Konstitusi menjadi alternatif yang relevan dalam konteks ini. Hakim Ad Hoc, dipilih berdasarkan keahlian dan pengalaman khusus di bidang hukum konstitusi, dapat membantu menangani perkara-perkara kompleks atau sensitif tanpa adanya konflik kepentingan yang merugikan proses peradilan. Langkah-langkah ini diharapkan dapat meningkatkan integritas dan kredibilitas Mahkamah Konstitusi, menjalankan fungsi-fungsinya sebagai lembaga penegak konstitusi yang bebas dari pengaruh eksternal, serta memperkuat kepercayaan masyarakat terhadap sistem peradilan konstitusi. Meskipun masih terdapat tantangan dalam implementasi mekanisme ini, seperti pemilihan hakim Ad Hoc yang tepat dan mekanisme pengawasannya.